Chronic effects of copper and zinc on the fish, Etroplus suratensis (Bloch, 1790) by continuous flow through (CFT) bioassay. (January 2019) - Don Xavier, N.D.; Bijoy Nandan, S.; Jayachandran, P.R.; Anu, P.R.; Midhun, A.M.; Mohan, D.
Abstract: Copper (Cu) and zinc (Zn) play a vital role in the growth and development, however increased uptake causes deleterious effects in normal functioning of organisms. We have demonstrated in this contribution the tolerance limit of Cu and Zn on Etroplus suratensis (pearl spot) by Continuous Flow Through (CFT) bioassay and the biomarker responses. The accumulation for Cu, Zn and selected trace metals (Cr, Cd, Ni and Pb) from field conditions, as well Geo-accumulation index (I geo ) and Contamination factor (C.F) suggested moderate to heavy pollution in the Cochin estuarine system. The 96 h LC50 values for Cu was 1.74 ± 0.04 mg L −1 and that for Zn was 24.36 ± 0.58 mg L −1 at 95% confidence interval. No observed effect concentration (NOEC) and low observed effect concentration (LOEC) for Cu and Zn were derived based on the survival rates. Chronic toxicity values for Cu and Zn were 0.23 mg L −1 and 2.005 mg L −1 respectively for 30 days period. The histological, biochemical, hematological and behavioral parameters showed significant variations at sublethal concentrations. Lamellar hyperplasia in gills, vacuolation combined with necrosis in liver, increased occurrence of melanomacrophage centres in spleen were noticed at chronic levels for both Cu and Zn. Tissue specific bioconcentration was observed for zinc and copper in gill and liver respectively, with least rate of bioconcentration observed in muscle tissues. Malaonate Dehydrogenase (MDH), Super oxide dismutase (SOD), Nonspecific esterase (EST) activity significantly varied compared to control at NOEC and LOEC values in both the metals. The hematological and genotoxic alterations as decrease in erythrocyte count, lymphocytes, hemoglobin concentration and hematocrit percentage were significantly reduced (p < 0.05) and increased thrombocytes and neutrophils, increased frequency of micronuclei, lobed, blebbed and notched nuclei and binucleate cells were characteristic for the metals at the sublethal concentrations. The frequency of behavioral changes remained significantly higher at chronic level than the control group. Thus such CFT based studies are important for precisely mapping the toxicity changes in organisms and also to develop suitable water quality guidelines. Highlights: Chronic toxicity values for Cu and Zn on Etroplus suratensis were 0.23 mg L −1 and 2.005 mg L −1 respectively. Analysis of water and sediment samples from Cochin estuary showed contamination from Cu and Zn. Tissue-specific pattern of bioaccumulation of Cu and Zn were observed during study. Evident biomarker changes in Etroplus suratensis were observed on exposure to Cu and Zn.